Uma clínica no coletivo: experimentações no Programa de Saúde da Família - Mendes, Vera Lúcia Ferreira (2004)
This thesis deals with collective clinical health care through the phenomenon of clinical availability in the area of public health, namely full basic health care. "Collective" is understood here as a multifaceted composition of heterogeneous elements and tendencies: personal, institutional, etc. In this sense, the phenomenon of clinical availability - rather than specific clinical disciplines - is about activating the potential to treat health problems according to the variables and processes that give rise to them. This study investigated the viability and pertinence of this positioning within the scope of a public policy of full basic health care. It was a case study of the clinical experiences (1998 - 2003) of the family health teams in the Qualis II - Family Health Program in the city of São Paulo, initially run by a partnership between the State Health Department and the Zerbini Foundation, now by the latter in conjunction with the Municipal Health Department. We concluded that the acquisition of clinical perspectives in the field of basic health care and, through such perspectives, at other levels of care and administration, was productive. It was also, however, very clear that this is not about substituting strategies for intervention and/or care models. On the contrary, clinical health care proves to be a powerful means of fostering openings and individual and/or collective (re)signification within health practices, because it provides for the unpredictability and untimeliness of the processes involved in illness and recovery, and thus does not serve as a model nor lend itself to macropolitical formulas. Key words: Clínical Health Gare; Subjectivity; Speech therapy; Public Health; Collective Health Gare; Basic Health Gare; Family Health Program